Interannual variability of cold domes northeast of Taiwan. Issue 13 (3rd July 2018) - Cheng, Yu-Hsin; Hu, Jiayu; Zheng, Quanan; Su, Feng-Chun
ABSTRACT: Multi-sensor data from different satellites were analysed to study the interannual variability of the cold domes northeast of Taiwan. From the empirical orthogonal function analysis of along-track satellite altimeter data and sea surface temperature, both revealed a cold dome phenomenon located at approximately 122°36´E and 25°24´N, and their principal components demonstrated a variation of 4–6 years. The cold dome variation correlates best with the Oceanic Niño index and poorly with Pacific Decadal Oscillation index. The forcing could be wind stress curl and Kuroshio volume transport, which produce an upwelling around the Men-Hua Canyon. Positive wind stress curl and the on-shelf water transport of the Kuroshio Current through the North Men-Hua Canyon increase the chance of the cold dome formation which may be responsible for the interannual variability of cold domes.